2018
DOI: 10.1016/j.rpor.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Absolute dose verification of static intensity modulated radiation therapy (IMRT) with ion chambers of various volumes and TLD detectors

Abstract: The 0.125 cc ion chamber measures the absolute dose of the isocenter more accurately compared to the 0.65 cc chamber. TLDs have good accuracy (within 3.0%) for absolute dose measurements of in-field points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…They measured doses of off-axis points 2 cm and 4 cm from the isocenter with TLDs. Acun-Bucht et al (2018) found the difference between TPS and TLD doses at 2cm and 4cm distance from the isocenter of approximately 3% and 4%, respectively (Acun-Bucht et al, 2018). In our current study, the difference between TLD and TPS doses for 2 cm and 4 cm distances from the isocenter is less than 1%.…”
Section: Resultssupporting
confidence: 43%
“…They measured doses of off-axis points 2 cm and 4 cm from the isocenter with TLDs. Acun-Bucht et al (2018) found the difference between TPS and TLD doses at 2cm and 4cm distance from the isocenter of approximately 3% and 4%, respectively (Acun-Bucht et al, 2018). In our current study, the difference between TLD and TPS doses for 2 cm and 4 cm distances from the isocenter is less than 1%.…”
Section: Resultssupporting
confidence: 43%
“…Chen et al obtained equivalent doses for organs or tissues of patients with nasopharyngeal carcinoma under the VMAT program and normal doses by inserting a TLD into human molds [22]. Acun-Bucht et al found that the TLD readings were consistent with the TPS calculations with a 3% deviation on the central axis in their dosimetric validation of the intensity-modulated radiotherapy (IMRT) scheme, providing a good accuracy for absolute dosimetry [23]. Lai et al evaluated the therapeutic dose at the nasopharyngeal air-tissue interface using an anthropomorphic model and found that the difference between the calculated TPS dose and measured TLD at the air-tissue interface under a 2 cm × 2 cm field of view was − 4.9% [24].…”
Section: Discussionmentioning
confidence: 99%